Vagus nerve stimulation for medically refractory absence epilepsy - Arya, Ravindra; Greiner, Hansel M.; Lewis, Amanda; Mangano, Francesco T.; Gonsalves, Cornelia; Holland, Katherine D.; Glauser, Tracy A. (Seizure (London, England), 2013)
A proportion of patients with childhood and juvenile absence epilepsies (CAE, JAE) are likely to be classified as medically refractory. In view of evidence gap for the treatment of such patients, this series is reported to generate estimate for efficacy of vagus nerve stimulation (VNS) in this patient population. Patients were identified by a chart review of all VNS recipients between January 1, 2006 and December 31, 2011. The diagnosis of CAE and JAE was based on conventional criteria. Details of demography, epilepsy phenomenology, management and outcomes were extracted. The outcome measures included reduction in daily seizure frequency measured as a percentage of pre-VNS seizure frequency and classified on International League Against Epilepsy (ILAE) outcome scale. Nine patients (7 CAE, 2 JAE) with a mean age of seizure onset of 5.4 years (±3.9) were identified. Mean duration of epilepsy prior to VNS implant was found to be 3.9 years (±1.4). These patients had failed a median of 5 anti-epileptic drugs before being referred for consideration of surgical treatment. After a mean follow-up of 33.9 months (±25.5, minimum 4 months), 1 patient attained complete seizure freedom (ILAE class 1), 6 had ILAE class 4 and 2 had ILAE class 5 outcomes, respectively. Mean reduction in daily seizure frequency was found to be 53.5±60.3% (1-sided p-value for paired t-test=0.04), with a 50% responder rate of 55.6%. VNS may be considered as a therapeutic option in patients with medically refractory absence epilepsy.